2021
DOI: 10.1101/2021.12.01.21266958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A six-month periodic fasting reduces microalbuminuria and improves metabolic control in patients with type 2 diabetes and diabetic nephropathy: a randomized controlled study

Abstract: AimNovel dietary interventions focused on fasting, have gained scientific and public attention. Periodic fasting has emerged as a dietary modification promoting beneficial effects on metabolic syndrome. This study aimed to assess whether periodic fasting reduces albuminuria in patients with type 2 diabetes and diabetic nephropathy and determine whether a reduction in albuminuria relates to activation of nephropathy-driven pathways.MethodsForty patients with type 2 diabetes (HbA1c 7.8±0.2% [62.1±2.3 mmol/mol]) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(42 reference statements)
0
1
0
1
Order By: Relevance
“…Similarly, higher body weight and BMI are negatively correlated with LDL cholesterol levels. These findings align with the established understanding that obesity is often accompanied by alterations in lipid profiles that contribute to an unfavorable cardiovascular risk profile [19][20].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, higher body weight and BMI are negatively correlated with LDL cholesterol levels. These findings align with the established understanding that obesity is often accompanied by alterations in lipid profiles that contribute to an unfavorable cardiovascular risk profile [19][20].…”
Section: Discussionsupporting
confidence: 88%
“… 31 The present study reported a significant change in albuminuria despite no change in serum creatinine, e-GFR, and incidence of nephropathy. Sulaj et al 32 also reported greater improvement in albuminuria with IF as compared with the Mediterranean diet and no difference in e-GFR or serum creatinine between the two groups.…”
Section: Discussionmentioning
confidence: 92%
“… 31 O presente estudo mostrou uma mudança significativa na albuminúria, sem alteração na creatinina sérica, TFGe, e incidência de nefropatia. Sulaj et al 32 também mostraram que o JI foi mais efetivo em melhorar a albuminúria em comparação à dieta mediterrânea, sem diferença na TFGe ou creatinina sérica entre os dois grupos.…”
Section: Discussionunclassified